2022
DOI: 10.1155/2022/1709918
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clock Genes Are Correlated with Prognosis and Immune Cell Infiltration in Colon Adenocarcinoma

Abstract: Background. Colon adenocarcinoma (COAD) is a malignancy with a high incidence and is associated with poor quality of life. Dysfunction of circadian clock genes and disruption of normal rhythms are associated with the occurrence and progression of many cancer types. However, studies that systematically describe the prognostic value and immune-related functions of circadian clock genes in COAD are lacking. Methods. Genomic data obtained from The Cancer Genome Atlas (TCGA) database was analyzed for expression lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…In hematological malignancies, BMAL1 expression levels correlate inversely with MYC levels [ 76 ], the PER genes are downregulated in CLL [ 97 ], NPAS2 is up-regulated in AML patients [ 98 ], and the CRY genes show both up- and down-regulation in CLL and AML [ 99 , 100 ]. Similar associations have been reported in other cancers, including head and neck [ 101 ], colorectal cancer [ 83 , 102 ], liver cancer [ 103 ], and lung cancer [ 104 , 105 ] to name but a few. Overall, the accumulated data point to the importance of circadian rhythms in normal health and suggest that interventions to normalize disrupted rhythms in obesity and cancer could be beneficial.…”
Section: Obesity and Cancer: Overview Of A Complex Relationshipsupporting
confidence: 76%
“…In hematological malignancies, BMAL1 expression levels correlate inversely with MYC levels [ 76 ], the PER genes are downregulated in CLL [ 97 ], NPAS2 is up-regulated in AML patients [ 98 ], and the CRY genes show both up- and down-regulation in CLL and AML [ 99 , 100 ]. Similar associations have been reported in other cancers, including head and neck [ 101 ], colorectal cancer [ 83 , 102 ], liver cancer [ 103 ], and lung cancer [ 104 , 105 ] to name but a few. Overall, the accumulated data point to the importance of circadian rhythms in normal health and suggest that interventions to normalize disrupted rhythms in obesity and cancer could be beneficial.…”
Section: Obesity and Cancer: Overview Of A Complex Relationshipsupporting
confidence: 76%
“…Per1-3 were reported to have tumour suppressor properties, but certain studies reached different conclusions (Table I). A total of seven studies determined that the expression of Per1 was significantly decreased in tumour tissue compared to healthy mucosa (37)(38)(39)(40)(41)(42)(43)(44). Furthermore, one study indicated a decrease in Per1 in undifferentiated tumours, while no differences were obtained in differentiated colon carcinomas (45), but two studies found no significant differences in Per1 between colon tumours and healthy mucosa (46,47).…”
Section: Associations Between Crc and Circadian Clock Genesmentioning
confidence: 99%
“…Hasakova et al (50,53) found that Per2 was downregulated in tumour tissues of male patients with CRC, but Krugluger et al (45) determined that Per2 expression exhibited no differences in colon tumour tissues; the following six studies also confirmed this (38,(40)(41)(42)47). Another six studies examined the gene expression of Per3 and all found significant decreases (37)(38)(39)41,42,54). In addition, Alexander et al (55) found a Per3 gene length polymorphism, and the 5-repeat Per3 VNTR sequence may increase the chance of colorectal adenoma formation.…”
Section: Associations Between Crc and Circadian Clock Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…According to one study, CLOCK, CRY1, and NR1D1 mRNA expression was raised in COAD tissue. A bioinformatic study revealed that circadian rhythm genes were mostly 5 Computational and Mathematical Methods in Medicine associated with the glucocorticoid receptor pathway [15]. However, the functions of CCGs in the colorectal cancer remained largely to be unclear.…”
Section: Introductionmentioning
confidence: 99%